Question and Answers Forum

All Questions      Topic List

Algebra Questions

Previous in All Question      Next in All Question      

Previous in Algebra      Next in Algebra      

Question Number 212181 by RojaTaniya last updated on 05/Oct/24

Answered by A5T last updated on 05/Oct/24

a^2 +b^2 +c^2 =(a+b+c)^2 −2(ab+bc+ca)=5  ⇒ab+bc+ca=2  a^3 +b^3 +c^3 −3abc=(a+b+c)[(a+b+c)^2 −3(ab+bc+ca)]  ⇒27−3abc=3[9−3(2)]=9⇒abc=6  ⇒a,b,c are roots of x^3 −3x^2 +2x−6=0  ⇒x^2 (x−3)+2(x−3)=(x−3)(x^2 +2)=0  (a,b,c)=(3,i(√2),−i(√2)) upto permutation  ⇒a^(100) +b^(100) +c^(100) =3^(100) +2^(50) +2^(50) =3^(100) +2^(51)

$${a}^{\mathrm{2}} +{b}^{\mathrm{2}} +{c}^{\mathrm{2}} =\left({a}+{b}+{c}\right)^{\mathrm{2}} −\mathrm{2}\left({ab}+{bc}+{ca}\right)=\mathrm{5} \\ $$$$\Rightarrow{ab}+{bc}+{ca}=\mathrm{2} \\ $$$${a}^{\mathrm{3}} +{b}^{\mathrm{3}} +{c}^{\mathrm{3}} −\mathrm{3}{abc}=\left({a}+{b}+{c}\right)\left[\left({a}+{b}+{c}\right)^{\mathrm{2}} −\mathrm{3}\left({ab}+{bc}+{ca}\right)\right] \\ $$$$\Rightarrow\mathrm{27}−\mathrm{3}{abc}=\mathrm{3}\left[\mathrm{9}−\mathrm{3}\left(\mathrm{2}\right)\right]=\mathrm{9}\Rightarrow{abc}=\mathrm{6} \\ $$$$\Rightarrow{a},{b},{c}\:{are}\:{roots}\:{of}\:{x}^{\mathrm{3}} −\mathrm{3}{x}^{\mathrm{2}} +\mathrm{2}{x}−\mathrm{6}=\mathrm{0} \\ $$$$\Rightarrow{x}^{\mathrm{2}} \left({x}−\mathrm{3}\right)+\mathrm{2}\left({x}−\mathrm{3}\right)=\left({x}−\mathrm{3}\right)\left({x}^{\mathrm{2}} +\mathrm{2}\right)=\mathrm{0} \\ $$$$\left({a},{b},{c}\right)=\left(\mathrm{3},{i}\sqrt{\mathrm{2}},−{i}\sqrt{\mathrm{2}}\right)\:{upto}\:{permutation} \\ $$$$\Rightarrow{a}^{\mathrm{100}} +{b}^{\mathrm{100}} +{c}^{\mathrm{100}} =\mathrm{3}^{\mathrm{100}} +\mathrm{2}^{\mathrm{50}} +\mathrm{2}^{\mathrm{50}} =\mathrm{3}^{\mathrm{100}} +\mathrm{2}^{\mathrm{51}} \\ $$

Commented by RojaTaniya last updated on 05/Oct/24

Sir thanks

$${Sir}\:{thanks} \\ $$

Answered by mr W last updated on 10/Oct/24

p_1 =e_1 =3  p_2 =e_1 p_1 −2e_2 =5 ⇒e_2 =2  p_3 =e_1 p_2 −e_2 p_1 +3e_3 =27 ⇒e_3 =6  p_n =e_1 p_(n−1) −e_2 p_(n−2) +e_3 p_(n−3)   r^3 −3r^2 +2r−6=0  r_1 =3, r_(2,3) =±(√2)i  p_n =3^n +2^(n/2) [i^n +(−i)^n ]=3^n +2^((n/2)+1) cos ((nπ)/2)  ⇒p_(100) =3^(100) +2^(51)

$${p}_{\mathrm{1}} ={e}_{\mathrm{1}} =\mathrm{3} \\ $$$${p}_{\mathrm{2}} ={e}_{\mathrm{1}} {p}_{\mathrm{1}} −\mathrm{2}{e}_{\mathrm{2}} =\mathrm{5}\:\Rightarrow{e}_{\mathrm{2}} =\mathrm{2} \\ $$$${p}_{\mathrm{3}} ={e}_{\mathrm{1}} {p}_{\mathrm{2}} −{e}_{\mathrm{2}} {p}_{\mathrm{1}} +\mathrm{3}{e}_{\mathrm{3}} =\mathrm{27}\:\Rightarrow{e}_{\mathrm{3}} =\mathrm{6} \\ $$$${p}_{{n}} ={e}_{\mathrm{1}} {p}_{{n}−\mathrm{1}} −{e}_{\mathrm{2}} {p}_{{n}−\mathrm{2}} +{e}_{\mathrm{3}} {p}_{{n}−\mathrm{3}} \\ $$$${r}^{\mathrm{3}} −\mathrm{3}{r}^{\mathrm{2}} +\mathrm{2}{r}−\mathrm{6}=\mathrm{0} \\ $$$${r}_{\mathrm{1}} =\mathrm{3},\:{r}_{\mathrm{2},\mathrm{3}} =\pm\sqrt{\mathrm{2}}{i} \\ $$$${p}_{{n}} =\mathrm{3}^{{n}} +\mathrm{2}^{\frac{{n}}{\mathrm{2}}} \left[{i}^{{n}} +\left(−{i}\right)^{{n}} \right]=\mathrm{3}^{{n}} +\mathrm{2}^{\frac{{n}}{\mathrm{2}}+\mathrm{1}} \mathrm{cos}\:\frac{{n}\pi}{\mathrm{2}} \\ $$$$\Rightarrow{p}_{\mathrm{100}} =\mathrm{3}^{\mathrm{100}} +\mathrm{2}^{\mathrm{51}} \\ $$

Commented by TonyCWX08 last updated on 08/Oct/24

Girand−Newton′s Identity?

$${Girand}−{Newton}'{s}\:{Identity}? \\ $$

Commented by mr W last updated on 08/Oct/24

yes

$${yes} \\ $$

Terms of Service

Privacy Policy

Contact: info@tinkutara.com